LO023: Association between ED-induced delirium and cognitive & functional decline in seniors. (2nd June 2016) - Giroux, M.; Émond, M.; Sirois, M.; Boucher, V.; Daoust, R.; Gouin, E.; Pelletier, M.; Voyer, P.; Lemire, S.; Berthelot, S.; Moore, L.; Lee, J.S.; et al.
Abstract : Introduction: Delirium is a common medical complication among seniors in hospital setting. In the emergency department (ED), its prevalence varies between 7 & 14%. Delirium is associated with increased mortality & longer hospital stay. This condition is also associated with functional & cognitive decline in hospitalized seniors and higher risk of institutionalization up to 2 years after their discharge. However, no data is currently available for ED patients. The aim of this study was to evaluate the association between ED-induced delirium and functional & cognitive decline in seniors at 60 days.Methods: This study is part of the Incidence and Impact measurement of Delirium Induced by ED-Stay (INDEED) study, an ongoing multicenter prospective cohort study in 5 Quebec EDs. Patients were recruited after 8 hours in the ED and followed up to 24h after admission. A 60-day follow-up phone assessment was also conducted. Delirium was measured by the validated Confusion Assessment Method & the Delirium Index. Functional status was measured by the validated OARS. Cognitive status was measured using the validated TICS-M. Functional and cognitive decline were obtained by comparing the baseline and 60-days follow-up scores.Results: 380 seniors were recruited and 280 had 60-day follow-up data available. ED-induced delirium was 8.4% of seniors. There was a difference in mean functional decline among seniors with and without ED-induced delirium 2.95(1.23-4.67) vs 1.55(1.20-1.91, pwlicoxon = 0.05] Proportion of seniors showing a decline ≥2 points on the OARS was significantly higher In those with ED-induced delirium (65, 0 % vs 40.18 %, p=0.03). Seniors with ED-induced delirium also showed a significant decline in mean TICS scores [3.31 (0, 82-5.84) vs -0.01((-.071-0.75)), pwlicoxon =0.009]. There was no significant difference in the proportions of seniors showing a decline ≥ 3 OARS points between those with or without delirium (p=0.06).Conclusion: ED-induced delirium seems to be associated with poor functional and cognitive outcomes in older patients 60 days after discharge from the hospital. Further studies are required to confirm clinical importance ED-induced delirium delayed complication.